PENGARUH PEMEKATAN KONSENTRASI FENOL DARI LINDI HITAM DALAM PEMBUATAN PEREKAT FENOL FORMALDEHIDA - R Sudradjat; E Yusnita; U Kulsum; E Kusmiati (Jurnal Penelitian Hasil Hutan, 2003)
This investigation was a successive series of experiments aimed at assessing the manufacture of phenol formaldehydeglue utilized the black liquor from soda-process-based pulp mill.At first,  the phenol in the black liquor was concentrated by adding crystal phenol.  The ratios in weight between crystal phenol as added and black liquor were consecutively 1:5, 1:10,  1: 15, 1:20, and 1:25,  and as such yielded the concentrated phenol in the liquor at four levels as well.The results  revealed that efficiency recovery of phenol obtained by vacuum distillation  was 12 percent.  Such efficiency was because most of the phenol  in black liquor was associated with  other elements  in  the lignin  structure  or  other  compounds. The phenol was further  reacted with formaldehyde, and the resulting phenol formaldehyde (PF) used as glue in plywood bonding.Results  revealed that moisture content  of plywood with  PF glue where the phenol was from  the mixture of concent tended black liquor's  phenol  and crystal phenol  varied at  8.80  to 9.61 percent. The moisture contended to increase with the increase in the ratio of crystal phenol to the black liquor distillate.The density of plywood was about 0.5710  - 0.6431  gram per cm3,  and tended to increasewith the increase in the ratio of crystal phenol  as well.                                                                                •The bonding strength  of plywood without boiling-treatment   was in the range of 11.173-23.722 kg per cm2, where by the lowest strength occurred at implementing 1 : 20 ratio (A4) and the highest at 1 : 5(A1). Meanwhile, the bonding-strength test with boiling-treatment  revealed the value at 1.924 - 18.306  kg per cm2 in that the lowest value was at 1 : 25 ratio (A5) and the highest at 1 : 5 ratio (Al).